Sound generation for the haptic perception using an irregular primitive function - Kim, S.-C.; Kwon, D.-S.; Kang, S.-C. (Proceedings - IEEE International Workshop on Robot and Human Interactive Communication, 2007)
In this paper, a sound synthetic technique (SST) based on sinusoidal frequency modulations with irregular primitive function algorithms for tactile perception is suggested. Investigations of the benefits of real-time SST for haptic interaction were referenced. Performance was evaluated in two ways; 1) a unimodal analysis of synthesized sounds in terms of whether they can induce tactile perception, and 2) multimodal analysis of the relationship between tactile perception and the generated sound. The unimodal analysis of sound suggested that meaningful spectrum contents can be generated using the proposed SST. The result of the multimodal analysis showed that auditory-haptic multimodal perception increases human sensitivity of texture perception. ？2007 IEEE.